Leveraging Diversity: The Department Chair’s Transformative Role - Edna Chun (Academic Chairpersons Conference Proceedings, 2016)
This workshop focuses on concrete research-based approaches and strategies to strengthen department chair leadership in the area of diversity. Since most of the chair literature is silent on this topic, the workshop draws on the extensive research findings of Edna Chun and Alvin Evans’ book, The Department Chair as Transformative Leader: Building Inclusive Learning Environments in Higher Education (Stylus, 2015) to share best practices and models that illuminate the role of the chair in building diversity in the academic department.
Keywords: concrete research-based approaches to strengthen department chairs leadership